Description of Heliocypha vantoli spec. nov. from Siberut in the Mentawai Islands (Odonata: Chlorocyphidae) - Hämäläinen, Matti (Zootaxa, 2016)
Heliocypha vantoli Hämäläinen, spec. nov. [holotype ♂ from Indonesia, Mentawai Islands (off Sumatra), Siberut Island, 29-31 January 2013, deposited at RMNH, Leiden, The Netherlands] is described and illustrated for both sexes and compared with the Heliocypha species found in Sumatra and adjacent small islands. Notes on the Odonata fauna of the Mentawai Islands are also provided. Euphaea aspasia Selys, 1853 (Euphaeidae) is recorded as new to these islands; differences in the colour pattern of the Siberut and mainland Sumatran specimens are briefly discussed.